THE EFFECT OF DIGITAL STORYTELLING ON TEACHER EDUCATION: EXPERIENCES OF PRE-SERVICE TEACHERS - Norkutė, Odeta; Jurgilė, Vaida; Ponomarenko, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Digital storytelling (DST) has emerged as a powerful tool in teacher education. However, in Lithuania the effect of this method on pre-service teachers’ education has been poorly investigated. The purpose of the current paper is to explore the experience of pre-service teachers in implementing DST method: from idea generation to the final product creation. The novelty of the current research is the usage of DST as a mean for development pre-service teachers’ ICT skills together with cooperation skills and creativity. The focus group interview method was implemented in order to collect the data and explore the opinions and experiences of perspective teachers. The research findings demonstrate that the usage of DST contributes to reveal student’ insights of future work, familiarizes students with future profession peculiarities, enhances their ability to cooperate, teamwork skills, and facilitates their ICT skills. The results highlight the importance of DST usage in developing perspective teacher’s creative personality and capability to interact.